2021
DOI: 10.3390/jintelligence9040053
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Game-Based Assessments for Hiring Autistic Job Seekers

Abstract: Although people with autism are protected under the Americans with Disabilities Act of 1990, there is little theoretical or practical effort to determine whether traditional pre-employment assessments unfairly impact autistic job seekers. Due to the lack of emphasis on social communication, game-based assessments (GBAs) may offer a way of assessing candidate ability without disadvantaging autistic candidates. A total of 263 autistic job seekers took one of two game-based assessment packages designed to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Barriers to the employment of autistic adults also include hiring processes that define talent too narrowly and the use of unstructured job interviews which may be biased against people with atypical manners of interaction (Willis et al, 2021; Wilson & Bishop, 2021). Even if they get hired, negative attitudes or stereotypes about customizing standardized job roles or tailoring working conditions to accommodate special needs are other challenges to overcome (Solomon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to the employment of autistic adults also include hiring processes that define talent too narrowly and the use of unstructured job interviews which may be biased against people with atypical manners of interaction (Willis et al, 2021; Wilson & Bishop, 2021). Even if they get hired, negative attitudes or stereotypes about customizing standardized job roles or tailoring working conditions to accommodate special needs are other challenges to overcome (Solomon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been recognition that DEI efforts should extend to groups beyond these demographic categories, such as individuals with disabilities and the neurodivergent community. As organizations build out diversity initiatives, navigating the balance between the growing social push for inclusion and the real challenges of accommodating neurodivergent workers across the talent lifecycle is coming into focus for research and applied work (Willis et al, 2021). Beyond reputational benefits, organizations across industries have pioneered a shift in the way they manage their workforces and have developed programs to attract and retain sources of untapped talent (Walkowiak, 2021).…”
Section: Neurodiversity: An Overviewmentioning
confidence: 99%
“…Much of the research that has been conducted is limited by small sample sizes or a narrow focus on one or two distinct neurodivergent conditions, commonly autism. A recent study (Willis et al, 2021) compared the test scores of autistic and nonautistic individuals on cognitive ability assessments measuring mathematical, memorization, and visuospatial skills in a game-based format. The study found no significant differences in performance between the two groups, suggesting that the assessments are unlikely to create disparities in outcomes (Willis et al, 2021).…”
Section: Neurodiversity: An Overviewmentioning
confidence: 99%
“…Technology enabled and game-based assessment are quickly gaining popularity. These types of assessments not only invite the opportunity to make assessment more engaging for different groups but also introduce a bevy of psychometric concerns, not the least of which is differential functioning by neurodiversity status (Willis et al, 2021). Forced choice items represent another item format that may prove challenging for neuroatypical applicants.…”
Section: Assessment Characteristicsmentioning
confidence: 99%